Retention of Urine after radical Hysterectomy for Cervical Cancer - Rana, Jyoti; Rong, Shi Hui; Mehata, Suresh (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
A total of 90 patients with cervical cancer, who underwent radical hysterectomy were included in this study. 25 patients, i.e. 27.8% were menopausal and 11 patients, i.e. 12.2% had blood loss more than 500ml. The patients with retention of urine after radical hysterectomy were compared in relation with loss of blood volume intra- operatively, parity, and menopause; as the possible causes of retention of urine. The overall frequency of retention of urine among the patients who underwent radical hysterectomy for the cervical cancer was 42.2%. The statistical analysis showed that the relation of urine after radical hysterectomy for cervical cancer with loss of blood volume, parity and menopause was found to be non-significant. DOI: http://dx.doi.org/10.3126/jmmihs.v1i1.9897 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(1) 2011; 24-29